PENGARUH METODE ONE DAY ONE PAGE TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SD NEGERI 106813 AMPLAS T.A 2025/2026 - Monika Nainggolan; Winara; Tiarnita Maria Sarjani Siregar; Husna Parluhutan Tambunan; Masta Marselina Sembiring (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted based on the low reading comprehension skills of fifth-grade students at SD Negeri 106813 Amplas, particularly in understanding inferential and evaluative information from reading texts. The study aimed to examine the effect of the One Day One Page method on students' reading comprehension skills. This research employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The population and sample consisted of all 46 fifth-grade students of SD Negeri 106813 Amplas in the 2025/2026 academic year, including 23 students in Class VA as the experimental group and 23 students in Class VB as the control group. Data were collected using a 30-item multiple-choice test at the C4-C6 cognitive levels, which had met the criteria of validity, reliability, item difficulty, and discrimination index. The experimental group was taught using the One Day One Page method, while the control group received conventional instruction. The findings revealed that the experimental group's mean pretest score increased from 59 to 88 in the posttest, whereas the control group's mean score increased from 63 to 75. The results of the Shapiro–Wilk normality test and Levene's Test indicated that the data were normally distributed and homogeneous. Furthermore, the Independent Samples t-test yielded a significance value of 0.000 (Sig. < 0.05) with a mean difference of 13.174, indicating that the alternative hypothesis was accepted. Therefore, the One Day One Page method had a significant effect on the reading comprehension skills of fifth-grade students at SD Negeri 106813 Amplas.